ANALISIS SIFAT-SIFAT PERMUKAAN BIRNESSITEYANG DIPREPARASI DARI DUA AGEN PEREDUKSI BERBEDA - Hartini Azhar; Amir Awaluddin; Akmal Muchtar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The layered manganese oxides having birnessite structure have been successfully synthesized using the two different types of reducing agents by solid-state ceramic method.  The reducing agent used  in  this  study was  oxalic acid and glucose.  Birnessite synthesized has been characterized using XRD, SEM and methylene blue adsorption. The XRD results indicated that the two types of reducing  agents produced mainly birnessite phases with different crystallinity .Birnessites  synthesized from two reducing agents have different surface properties as indicated from data of SEM and methylene blue adsorption.